KNOWLEDGE, ATTITUDE AND PRACTICES REGARDING NEEDLESTICK INJURIES AMONG DENTAL STUDENTS - Kumar mp, Santhosh (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To assess the knowledge, attitude and practices among dental students on needle stick injuries (NSIs). Methods: A validated questionnaire of 23 questions regarding the basic knowledge, attitude and practices about NSIs was distributed among 100 students randomly belonging to 3 rd year, final year, and internship (5 year trainee) of undergraduate dental program in Saveetha Dental College and Hospital, Saveetha University, Chennai. The data extracted were tabulated, statistically analyzed and results obtained. Results were calculated on the basis of frequency and percentages using SPSS. th Results: About 87% of students had received hepatitis B (HBs) vaccination of which only 47% had carried out anti-HBs antibody check-up. Although 35% had suffered NSI, 15% of them did not report the incident of NSIs. However, only 37% of students knew about Universal Precaution guidelines. 76% of students had the habit of recapping the needle after injection. Conclusion: This study revealed that knowledge of dental students about the risks associated with NSIs and use of preventive measures was inadequate. A standard protocol regarding the training as well as adapting preventive measures should be formulated in all dental institutions. The implementation of Universal Precautions, elimination of needle recapping, use of safer needle devices, and use of sharps containers for safe disposal will reduce NSIs. Keywords: Knowledge, Awareness, Needle stick injuries, Universal Precaution Guidelines, Hepatitis B, Hepatitis C, Health-care workers.